2018
DOI: 10.1016/s2352-3018(18)30024-9
|View full text |Cite
|
Sign up to set email alerts
|

The global Optima HIV allocative efficiency model: targeting resources in efforts to end AIDS

Abstract: World Bank and Australian NHMRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 13 publications
3
56
0
Order By: Relevance
“…Whenever country teams work with the Optima HIV model, our recommendation has been to explicitly model 90-90-90 targets and many countries chose to do so in the original studies using the model. Our research using Optima HIV has also demonstrated that scaling-up treatment is typically of highest priority for most countries [10], and this was also a key result in the studies summarized in this article.While we collectively aspire to full coverage of all services for all people in need, especially including testing and treatment, the unfortunate reality is that complete implementation of 90-90-90/95-95-95 may not be feasible to implement in some contexts. The letter and modelling studies by Granich, Gupta and Williams advocate for testing everyone in high-prevalence settings once or twice a year and providing immediate treatment [2].…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Whenever country teams work with the Optima HIV model, our recommendation has been to explicitly model 90-90-90 targets and many countries chose to do so in the original studies using the model. Our research using Optima HIV has also demonstrated that scaling-up treatment is typically of highest priority for most countries [10], and this was also a key result in the studies summarized in this article.While we collectively aspire to full coverage of all services for all people in need, especially including testing and treatment, the unfortunate reality is that complete implementation of 90-90-90/95-95-95 may not be feasible to implement in some contexts. The letter and modelling studies by Granich, Gupta and Williams advocate for testing everyone in high-prevalence settings once or twice a year and providing immediate treatment [2].…”
supporting
confidence: 55%
“…Whenever country teams work with the Optima HIV model, our recommendation has been to explicitly model 90-90-90 targets and many countries chose to do so in the original studies using the model. Our research using Optima HIV has also demonstrated that scaling-up treatment is typically of highest priority for most countries [10], and this was also a key result in the studies summarized in this article.…”
supporting
confidence: 55%
“…If all this is in place, it means that the condom use will be effective. This study population comprised teenagers, with the majority being between the ages of 15 and 17 years (64.5%, n = 223), mostly in grade 11, and they were deemed high-risk for HIV and AIDS because HIV prevalence is highest amongst this age group (7.2 million people living with HIV) [22]. Furthermore, these learners have been reported to have the highest rate of pregnancies (n = 45 [6.6%]) in the circuit [23].…”
Section: Discussionmentioning
confidence: 99%
“…Others have explored whether monotherapy or dual therapy can be used safely to reduce costs [12][13][14][15]. Strategic use of newly available generic antiretroviral (ARV) drugs has now entered the cost discussion in high-income countries, with modelling studies projecting significant savings from any increased use of generic ART [16][17][18][19][20][21]. De-simplifying or switching a single-tablet formulation (STF) to two or more tablets (i.e.…”
Section: Introductionmentioning
confidence: 99%